Anti-inflammatory effects of Pikad Tri-phol-sa-mut-than remedy, consisting of dried fruits of Aegle marmelos (L.) Corrêa, Coriandrum sativum L., and Morinda citrifolia L. (15th November 2022) - Tan, Bing; Chiranthanut, Natthakarn; Chansakaow, Sunee; Sireeratawong, Seewaboon; Khonsung, Parirat; Nimlamool, Wutigri; Takuathung, Mingkwan Na; Lertprasertsuke, Nirush
Abstract: Ethnopharmacological relevance: Inflammation has been known to possess some essential roles in many diseases, especially those with chronic or severe conditions. Pikad Tri-phol-sa-mut-than, a Thai traditional herbal remedy, has long been used to treat gastrointestinal sicknesses, fever, and severe illness caused by the deformities of Tridosha. In particular, this recipe has also been applied for inflammation-related conditions including gout and rheumatoid arthritis. The Pikad Tri-phol-sa-mut-than recipe consists of dried fruits of three herbs including Aegle marmelos (L.) Corrêa, Morinda citrifolia L., and Coriandrum sativum L. Each of these plant components of Pikad Tri-phol-sa-mut-than exhibited anti-inflammatory activities. However, anti-inflammatory effect of Pikad Tri-phol-sa-mut-than remedy has not been reported. Aim of the study: The objective of this study was to elucidate the anti-inflammatory activities of Pikad Tri-phol-sa-mut-than extract (TS) against acute and chronic inflammation in rats. Materials and methods: To study the effects of TS on acute inflammation, ethyl phenylpropiolate (EPP)-induced ear edema, carrageenan- and arachidonic acid (AA)-induced hind paw edema models were carried out. In addition, cotton pellet-induced granuloma formation was performed to specify the inhibitory effects of TS on chronic inflammation. Results: The topical application of TS significantly inhibited EPP-induced ear edema in rats. In the carrageenan- and AA-induced paw edema models, the oral administration of TS significantly reduced paw volumes, compared to those of the control groups. In addition, the 7-day oral treatment of TS demonstrated a significant suppressive effect on cotton pellet-induced granuloma formation. Conclusions: The current study revealed that TS possesses anti-inflammatory activities against acute and chronic inflammation. Our studies support the use of TS in traditional medicine, and the development of TS as a novel natural product for treating diseases associated with inflammation. Graphical abstract: Image 1 Highlights: Pikad Tri-phol-sa-mut-than extract (TS) reduces edema in acute inflammation models. TS suppresses chronic inflammation in granuloma formation model. Caffeic acid may be an active constituent responsible for anti-inflammatory effects. Our findings support traditional uses of this remedy.